Self‐organized Ruthenium–Barium Core–Shell Nanoparticles on a Mesoporous Calcium Amide Matrix for Efficient Low‐Temperature Ammonia Synthesis. Issue 10 (2nd February 2018) - Kitano, Masaaki; Inoue, Yasunori; Sasase, Masato; Kishida, Kazuhisa; Kobayashi, Yasukazu; Nishiyama, Kohei; Tada, Tomofumi; Kawamura, Shigeki; Yokoyama, Toshiharu; Hara, Michikazu; Hosono, Hideo
Abstract: A low‐temperature ammonia synthesis process is required for on‐site synthesis. Barium‐doped calcium amide (Ba‐Ca(NH2 )2 ) enhances the efficacy of ammonia synthesis mediated by Ru and Co by 2 orders of magnitude more than that of a conventional Ru catalyst at temperatures below 300 °C. Furthermore, the presented catalysts are superior to the wüstite‐based Fe catalyst, which is known as a highly active industrial catalyst at low temperatures and pressures. Nanosized Ru–Ba core–shell structures are self‐organized on the Ba‐Ca(NH2 )2 support during H2 pretreatment, and the support material is simultaneously converted into a mesoporous structure with a high surface area (>100 m 2  g −1 ). These self‐organized nanostructures account for the high catalytic performance in low‐temperature ammonia synthesis. Abstract : Ruthenium–barium core–shell nanoparticles and a mesoporous calcium amide matrix (Ru/Ba‐Ca(NH2 )2 ) self‐organize during treatment with hydrogen gas. The resultant composite material presents much higher catalytic performance in low‐temperature ammonia synthesis than other ruthenium catalysts and an industrial iron catalyst.